Il valore della tecnica per lo sviluppo integrale della persona umana nella "Caritas in Veritate" - Barrajón LC, Pedro (Alpha Omega, 2010)
The article reflects upon the social doctrine of the Catholic Church on the value of the technique. The first part presents the value of the technique according to one of the main do-cuments of the Second Vatican Council,“Gaudium et Spes” The Council is very open to the use of the techique of the real development of men and societies if the technique respects God’s plan for man and is at the service of the person. In the Encyclical Pope Benedict XVI “Caritas in Ve-ritate,” we find a whole chapter, the last one, on this subject. Here the Pope begins the reflec-tion on the technique at the basis of the major horizon of the anthropological, spiritual and ethi-cal perspectives. Then he presents four items in which the use of the technique offers important ethical aspects for Christian life and the life of the Church: peace, mass media, bioethics and psychology. Specially, this last aspect is really new, as considered in a Papal Encyclical of so-cial doctrine. To give an integral response to all the questions which have arisen in all these fields, it is important to have a solid point of reference and an integral anthropology that does not deny the existence and value of human spirituality.